Protection of integrity and ownership of pdf documents using invisible signature - Taha, Imad; Zeki, Akram M.; Pathan, Al-Sakib Khan; makarim, rusydi (IEEE digital library, 2012)
Distributing digital document through insecure channel leads to the question of the integrity and the ownership of the file on the receiver’s side. Employing hash function and digital signature algorithms solves the difficulties of the receiver to proof the approval of the document from the sender as well as detecting if the file has been altered by illegitimate parties. In this paper, a method to attach digital signature in Portable Document File (PDF) as invisible watermark is proposed. We show that the space character that splits the field in crossreference table can be overwritten without corrupting the file. The method to embed and extract the signature are proven to be efficient, since the offset index for cross-reference table are available at the end of the file. Our proposed method to embed the signature in the PDF file does not increase the size of the file and offer flexibility for the user to implements the digital signature scheme of his/her own preference.